2010
DOI: 10.1038/mi.2010.41
|View full text |Cite|
|
Sign up to set email alerts
|

TLR4/MyD88-induced CD11b+Gr-1intF4/80+ non-migratory myeloid cells suppress Th2 effector function in the lung

Abstract: In humans, environmental exposure to a high dose of lipopolysaccharide (LPS) protects from allergic asthma the immunological underpinnings of which are not well understood. In mice, exposure to a high LPS dose blunted house dust mite-induced airway eosinophilia and Th2 cytokine production. While adoptively transferred Th2 cells induced allergic airway inflammation in control mice, they were unable to do so in LPS-exposed mice. LPS promoted the development of a CD11b+Gr1intF4/80+ lung-resident cell resembling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(164 citation statements)
references
References 60 publications
9
154
1
Order By: Relevance
“…For example, influenza virus infection protects against infection from the unrelated respiratory syncytial virus (52), and heat-labile Escherichia coli toxin enhances protection to subsequent influenza or respiratory syncytial virus infection (53). Furthermore, in humans, exposure to high levels of LPS inhibits allergies and allergic asthma (54), whereas exposure of mouse lungs to LPS prior to or concomitant with allergen sensitization inhibits development of AAI following allergen challenge (55,56). This process of innate imprinting is thought to operate by various mechanisms including impairment of pulmonary APC function (53) or induction of regulatory myeloid-derived suppressor cells (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, influenza virus infection protects against infection from the unrelated respiratory syncytial virus (52), and heat-labile Escherichia coli toxin enhances protection to subsequent influenza or respiratory syncytial virus infection (53). Furthermore, in humans, exposure to high levels of LPS inhibits allergies and allergic asthma (54), whereas exposure of mouse lungs to LPS prior to or concomitant with allergen sensitization inhibits development of AAI following allergen challenge (55,56). This process of innate imprinting is thought to operate by various mechanisms including impairment of pulmonary APC function (53) or induction of regulatory myeloid-derived suppressor cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in humans, exposure to high levels of LPS inhibits allergies and allergic asthma (54), whereas exposure of mouse lungs to LPS prior to or concomitant with allergen sensitization inhibits development of AAI following allergen challenge (55,56). This process of innate imprinting is thought to operate by various mechanisms including impairment of pulmonary APC function (53) or induction of regulatory myeloid-derived suppressor cells (56). Our previous study (11) demonstrated an analogous inhibition of AAI with PS50G nanoparticles mediated via modification of pulmonary DC function.…”
Section: Discussionmentioning
confidence: 99%
“…25 They are potent suppressors of T-cell functions. Recent reports provide evidence that MDSCs can be induced in BM cultures by IL-6 26 or lipopolysaccharide 27,28 treatment in vitro and in murine airways 28 and can suppress Th2 effector functions. Intense cross-talk between TLR and C5aR signaling has been shown previously.…”
Section: Suggest That C5armentioning
confidence: 99%
“…25 MDSCs can be induced in vitro 27 and in vivo in the lung by activation of the TLR4/MyD88 pathway and suppress allergen-induced airway inflammation. 28 Further, distinct MDSC populations accumulate in the lung during experimental allergic asthma that either enhance or suppress T-cell responses. 45 Wt and C5aR SCs both expressed arginase-1 and NOS2, the latter of which was significantly higher in C5aR SCs.…”
Section: Cd11cmentioning
confidence: 99%
“…The study by Arora et al indicated that lipopolysaccharide (LPS)-induced CD11b Ï© Gr1 int cells in the lungs affected Th2 cell stability and could prevent allergic airway inflammation. These populations of cells that were induced in a MyD88-and TLR4-dependent manner have been shown to inhibit airway inflammation in an IL-10-and arginase I-dependent manner (20). Additionally production of nitric oxide synthase (NOS) (48) and IFN-␄ by these cells has also been attributed to their suppressive ability (20,49).…”
Section: Gr1mentioning
confidence: 99%